Segmented importance-performance analysis in whale-watching: Reconciling ocean coastal tourism with whale preservation. (15th February 2023) - Suárez-Rojas, Chaitanya; González Hernández, Matías; León, Carmelo J.
Abstract: Whale-watching faces the dual challenge of ensuring whale welfare and preserving marine environments in coastal areas and the open ocean while providing a satisfactory tourism experience. This study shows that importance-performance analysis (IPA), in combination with cluster analysis, provides insights into how to tailor the segments for the sustainable management of whale-watching. The segmentation analysis reveals differences in the perceptions of the activity's importance between specialist and generalist whale-watching tourists. These differences concern the factors relating to observation performance, learning about whale culture and preservation and a comfortable trip. The results suggest that operators may increase competitive advantage by focusing on those product features that are ecologically compatible, as well as investing in education and innovation. Moreover, from the point of view of coastal and ocean management and governance, the identification of consumer segments with ecological preferences raises opportunities to work towards sustainability. Graphical abstract: Image 1 Highlights: Whale-watching performance is evaluated employing a segmented-IPA analysis. Four tourist segments are found: recreationists, amateurs, passionate and committed. Segmentation analysis proves there is scope for higher ecological segments. Tailored, segmented whale-watching experiences work towards sustainability.